The Influence of Learning Media Based on Local Wisdom on the Social Studies Learning Motivation of Grade 4 Students of SDN Sedatigede 2: Pengaruh Media Pembelajaran Berbasis Kearifan Lokal Terhadap Motivasi Belajar IPS Siswa Kelas 4 SDN Sedatigede II - Fatmawati, Arum; Wati, Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2020)
This research aims to determine the influence and how much influence The use of local wisdom-based learning media towards student motivation. Local wisdom-based learning media is a learning medium in which there is information about local wisdom-regional wisdom of residential areas. The method in this research is pre-experimental design of one-group form pretest-posttest design and quantitative descriptive is the approach used. The results of this study were obtained from before the treatment and after treatment was given. This research was conducted at SDN Sedatigede II in class 4 with research subjects numbering 30 students and use nonprobability sampling with saturated sampling type. The instruments in this study are a poll. Data analysis results show average pretests value of 60.7 and average posttest value of 64.6 showing the influence of local wisdom-based learning media.Then from N-Gain calculation shows 0.31 results with moderate influence level criteria.